Barry, the bravest Saint Bernard - "Hall, Lynn" (Random House: New York, 1992)
Relates the feats of Barry, the St. Bernard dog whose name, to this day, honors the best dog at the St. Bernard Monastery
Keywords: Dog Juvenile-literature